A child in the social exclusion process - Kotradyová, Katarína; Rosková, Lenka (Journal of Nursing, Social Studies and Public Health, 2014)
The social exclusion is a serious global problem, and the social exclusion of the child has not been examined in a more conceptual way so far. Our main objective is to refer to the social exclusion of the child as to a dimension to which attention is not paid adequately, although it belongs to serious negative phenomena of multi-dimensional nature. The introduction deals with historical and European context of the social exclusion. On the basis of a system analysis we created two groups of subsets by categorization from a set of propositions concerning the social exclusion, namely the category of reasons of the social exclusion and the category of general characteristics of individuals that are in the process of social exclusion. Subsequently, we describe the reasons of the social exclusion of children, specifying and causally designating the subjects that initiate the social exclusion of children. We believe that whether the social exclusion of the child is caused by his/her parents or by another factor we cannot understand it only within an individual failure as external reasons also exist where it is a failure of several structures that can ensure a needed social integration of children within social activities. We point out that, in terms of the social exclusion of the child, we cannot focus only on monetary and consumption dimension of parents but also on the dynamics of the process of social exclusion when the child is integrated into the process of social exclusion by force without his/her effort as his/her outlook for the future is weak due to external factors. Finally, we refer to the consequences that the social exclusion of children can have for the whole climate in the society in the future, especially, for its stability and prevention of socio-pathologic phenomena.
Keywords: společenská třída; Family; terminologie jako téma; Terminology as Topic; interpersonální vztahy; Child; lidé; Social Behavior; Interpersonal Relations; Social Isolation; rodina; dítě; sociální izolace; sociální chování; Social Class; Humans